Identification, Characterization, and Palynology of High-Valued Medicinal Plants - Hina Fazal; Nisar Ahmad; Bilal Haider Abbasi (The Scientific World Journal)
High-valued medicinal plants Achillea millefolium, Acorus calamus, Arnebia nobilis, Fumaria indica, Gymnema sylvestre, Origanum vulgare, Paeonia emodi, Peganum harmala, Psoralea corylifolia, Rauwolfia serpentina, and Vetiveria zizanioides were identified with the help of taxonomical markers and investigated for characterization and palynological studies. These parameters are used to analyze their quality, safety, and standardization for their safe use. Botanical description and crude drug description is intended for their quality assurance at the time of collection, commerce stages, manufacturing, and production. For this purpose the detailed morphology was studied and compared with the Flora of Pakistan and other available literatures. Here we reported the pollen grain morphology of Origanum vulgare, Paeonia emodi, Psoralea corylifolia, and Rauwolfia serpentina for the first time. Similarly the crude drug study of Gymnema sylvestre (leaf), Origanum vulgare (aerial parts), Paeonia emodi (tubers), and Peganum harmala (seeds) was also carried out for the first time.